Exploratory Review and In Silico Insights into circRNA and RNA-Binding Protein Roles in γ-Globin to β-Globin Switching - Alawi Habara (Cells)
β-globin gene cluster regulation involves complex mechanisms to ensure proper expression and function in RBCs. During development, switching occurs as γ-globin is replaced by β-globin. Key regulators, like BCL11A and ZBTB7A, repress γ-globin expression to facilitate this transition with other factors, like KLF1, LSD1, and PGC-1α; these regulators ensure an orchestrated transition from γ- to β-globin during development. While these mechanisms have been extensively studied, circRNAs have recently emerged as key contributors to gene regulation, but their role in β-globin gene cluster regulation remains largely unexplored. Although discovered in the 1970s, circRNAs have only recently been recognized for their functional roles, particularly in interactions with RNA-binding proteins. Understanding how circRNAs contribute to switching from γ- to β-globin could lead to new therapeutic strategies for hemoglobinopathies, such as sickle cell disease and β-thalassemia. This review uses the circAtlas 3.0 database to explore circRNA expressions in genes related to switching from γ- to β-globin expression, focusing on blood, bone marrow, liver, and spleen. It emphasizes the exploration of the potential interactions between circRNAs and RNA-binding proteins involved in β-globin gene cluster regulatory mechanisms, further enhancing our understanding of β-globin gene cluster expression.